Pertussis Prevention: Reasons for Resurgence, and Differences in the Current Acellular Pertussis Vaccines - Esposito, Susanna; Stefanelli, Paola; Fry, Norman K.; Fedele, Giorgio; He, Qiushui; Paterson, Pauline; Tan, Tina; Knuf, Markus; Rodrigo, Carlos; Weil Olivier, Catherine; Flanagan, Katie L.; Hung, Ivan; et al. (Frontiers in Immunology, 2019)
Pertussis is an acute respiratory disease caused by Bordetella pertussis. Due to the frequency and severity of this disease, prevention of pertussis has been considered an important public health issue for many years. The development of the whole-cell pertussis vaccine (wPV) and its introduction into the paediatric immunization schedule was associated with a marked reduction in pertussis cases in the vaccinated cohort. However, due to the frequency of local and systemic adverse events after immunization with wPV, work on a less reactive vaccine was undertaken based on B. pertussis components that induced protective immune responses with fewer local and systemic reactions. These component vaccines were termed acellular vaccines and were composed of one or more pertussis antigens, including pertussis toxin (PT), filamentous haemagglutinin (FHA), pertactin (PRN), and fimbrial proteins 2 (FIM2) and 3 (FIM3). Preparations containing up to 5 components were developed, and several efficacy trials clearly demonstrated that the aPVs were able to confer similar or only slightly lower short-term protection than the most effective wPVs with fewer local and systemic reactions. Several factors could explain the resurgence of pertussis observed in recent years. Among them, the use of aPVs. This paper reports the results of a Consensus Conference that was organized by World Association for Infectious Disease and Immunological Disorders (WAidid) on June 22, 2018, in Perugia, Italy, and involved with the main aim of evaluating what are the most important reasons of pertussis resurgence and if there is a possible relationship between aPV use and increasing pertussis incidence rates, possibly taking into account differences among the aPVs presently available.